(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This study analyzes the national and cultural foundations of cyberonyms created by internet users and the strategies through which identity is expressed via these names. Nicknames, domain names, and other online onyms are examined from a linguocultural perspective. The findings indicate that users often rely on traditional naming models, religious components, and national values. At the same time, hybrid naming strategies are emerging under the influence of global internet culture. The study highlights the significance of cyberonomastics in contemporary linguistics.